High intensity interval and moderate continuous cycle training in a physical education programme improves health-related fitness in young females - Mazurek, K; Zmijewski, P; Krawczyk, K; Czajkowska, A; Kęska, A; Kapuściński, P; Mazurek, T (Biology of Sport, 2016)
The aim of the study was to investigate the effects of eight weeks of regular physical education classes supplemented with high intensity interval cycle exercise (HIIE) or continuous cycle exercises of moderate intensity (CME). Forty-eight collegiate females exercising in two regular physical education classes per week were randomly assigned to two programmes (HIIE; n=24 or CME; n=24) of additional (one session of 63 minutes per week) physical activity for 8 weeks. Participants performed HIIE comprising 2 series of 6x10 s sprinting with maximal pedalling cadence and active recovery pedalling with intensity 65%–75% HRmax or performed CME corresponding to 65%-75% HRmax. Before and after the 8-week programmes, anthropometric data and aero- and anaerobic capacity were measured. Two-way ANOVA revealed a significant time main effect for VO2max (p<0.001), similar improvements being found in both groups (+12% in HIIE and +11% in CME), despite body mass not changing significantly (p=0.59; +0.4% in HIIE and -0.1% in CME). A significant main time effect was found for relative fat mass (FM) and fat-free mass (FFM) (p<0.001 and p<0.001, respectively). A group x time interaction effect was found for relative FM and FFM (p=0.018 and p=0.018); a greater reduction in FM and greater increase in FFM were noted in the CME than the HIIE group. Improvements in anaerobic power were observed in both groups (p<0.001), but it was greater in the HIIE group (interaction effect, p=0.022). Weight loss is not mandatory for exercise-induced effects on improving aerobic and anaerobic capacity in collegiate females. Eight weeks of regular physical education classes supplemented with CME sessions are more effective in improving body composition than physical education classes supplemented with HIIE sessions. In contrast to earlier, smaller trials, similar improvements in aerobic capacity were observed following physical activity with additional HIIE or CME sessions.